Stereodynamic control of star-epoxy/anhydride crosslinking actuated by liquid-crystalline phase transitions. Issue 10 (7th February 2017) - Pin, Jean-Mathieu; Mija, Alice; Sbirrazzuoli, Nicolas
Abstract : The first observation of an anti-Arrhenius behavior in the crosslinking polymerization field associated with liquid-crystalline transition events. Abstract : The epoxy/anhydride copolymerization kinetics of an original star-epoxy monomer (TriaEP) was explored in dynamic heating mode using a series of isoconversional methods. Negative values of the apparent activation energy ( E α ) related to an anti-Arrhenius behavior were observed. The transition from Arrhenius to anti-Arrhenius behavior and vice versa depending on the E α of polymerization was correlated with the dynamics of mesophasic fall-in/fall-out events, physically induced transition (PIT) and chemically induced transition (CIT). This self-assembly phenomenon induces the generation of an anisotropic crosslinked architecture exhibiting both nematic discotic (ND ) and nematic columnar (NC ) organization. Particular emphasis was placed on evaluating the juxtaposition/contribution of the liquid-crystalline transitions to crosslinking, considering both the reaction dynamics and the macromolecular vision.